Pelatihan Public Speaking untuk Peningkatan Keterampilan Berbicara Anak dalam Bahasa Inggris di Rusunawa Jatinegara Kaum - Fatkhiyati, Nurrahma; Tesaannisa, Tesaannisa; Diyantari, Diyantari; Mardiana, Rizdika; Purbasari, Rahayu; Aurora, Zaneta; Belinda, Prishiella (Lembaga Dongan Dosen, 2024)
The community service program aims to provide public speaking training to strengthen the character of children aged 9-12 and develop their speaking skills in English while boosting their confidence. By giving them opportunities to speak in public, the program hopes to help them build strong self-confidence, particularly in using the English language. The method used in this community service program is participatory observation to identify the skills gap that needs to be addressed in the participants, which is expected to provide solutions for improving their abilities. Additionally, this training employs pre-tests and post-tests to assess improvements in English language skills and surveys to gather feedback from participants. The results of the activity demonstrate effectiveness in enhancing participants' communication and public speaking abilities, as well as improving their English language skills, as evidenced by the pre-test and post-test results.